Engineering self-organising helium bubble lattices in tungsten - R. W. Harrison (Nature Portfolio, 2017)
Abstract The self-organisation of void and gas bubbles in solids into superlattices is an intriguing nanoscale phenomenon. Despite the discovery of these lattices 45 years ago, the atomistics behind the ordering mechanisms responsible for the formation of these nanostructures are yet to be fully elucidated. Here we report on the direct observation via transmission electron microscopy of the formation of bubble lattices under He ion bombardment. By careful control of the irradiation conditions, it has been possible to engineer the bubble size and spacing of the superlattice leading to important conclusions about the significance of vacancy supply in determining the physical characteristics of the system. Furthermore, no bubble lattice alignment was observed in the <111> directions pointing to a key driving mechanism for the formation of these ordered nanostructures being the two-dimensional diffusion of self-interstitial atoms.